Cultural performances of cod - at Tromsø University Museum - Maurstad, Anita (Tidsskrift for kulturforskning, 2010)
Whereas museums traditionally present the nature of the natural sciences or the culture of the cultural sciences, Tromsø University Museum has recently presented an exhibition of the cultural performances of nature. The cod, the exhibition says - an important fish in many of the western coastal societies - is assigned various societal and cultural missions and its nature depends on who speaks for it. This article addresses the process of building the exhibition. A team of researchers and designers played supplementary roles in answering the challenge of communicating performative and constructivist perspectives on knowledge production within the frames of the museum institution, an institution traditionally known for displaying knowledge on nature as facts, not as enacted and negotiated products.